2017
DOI: 10.1016/j.jid.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Somatic Mutations in Primary Cutaneous Diffuse Large B-Cell Lymphoma, Leg Type by Massive Parallel Sequencing

Abstract: To determine whether the mutational profile of primary cutaneous diffuse large B-cell lymphoma, leg type (PCLBCL-LT) is unique by comparison with other diffuse large B-cell lymphoma subtypes, we analyzed a total cohort of 20 PCLBCL-LT patients by using next-generation sequencing with a lymphoma panel designed for diffuse large B-cell lymphoma. We also analyzed 12 pairs of tumor and control DNA samples by whole-exome sequencing, which led us to perform resequencing of three selected genes not included in the ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 51 publications
6
86
3
1
Order By: Relevance
“…Most cases are MUM‐1/IRF‐4 and bcl‐6 positive, CD10 negative, and have a gene expression profile resembling activated B cells . Perhaps not surprisingly, the genetic landscape observed in PCDLBCL, LT is similar to that observed in activated B‐cell‐type diffuse large B‐cell lymphoma (ABC‐DLBCL), with NF‐κB‐activating mutations being observed in CD79B, CARD11, and MYD88 . Of these, somatic MYD88 L265P mutations appear most common with a prevalence rate of ≈75% .…”
Section: Diagnosismentioning
confidence: 95%
“…Most cases are MUM‐1/IRF‐4 and bcl‐6 positive, CD10 negative, and have a gene expression profile resembling activated B cells . Perhaps not surprisingly, the genetic landscape observed in PCDLBCL, LT is similar to that observed in activated B‐cell‐type diffuse large B‐cell lymphoma (ABC‐DLBCL), with NF‐κB‐activating mutations being observed in CD79B, CARD11, and MYD88 . Of these, somatic MYD88 L265P mutations appear most common with a prevalence rate of ≈75% .…”
Section: Diagnosismentioning
confidence: 95%
“…In contrast, a SOCS1 mutation was detected in the tumor of subcutaneous tissue in TP44 (). SOCS1 mutations are known to be more prevalent in primary cutaneous diffuse large B‐cell lymphoma, leg type compared to DLBCL NOS . Therefore, somatic mutations in these genes may bias the location of tumors.…”
Section: Discussionmentioning
confidence: 96%
“…SOCS1 mutations are known to be more prevalent in primary cutaneous diffuse large B-cell lymphoma, leg type compared to DLBCL NOS. 18 Therefore, somatic mutations in these genes may bias the location of tumors. These results suggest that the paired tumors originate from divergent evolution of CPC through accumulation of distinct mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence in situ hybridisation analysis was positive for MYC gene locus rearrangement (Schrader et al , ; Zhou et al , ) and revealed clonal copy number gains of MYC and BCL2 . Monoclonal rearrangement of immunoglobulin heavy ( IGH ) chain was found and mutational analysis revealed a KRAS point mutation p.A146V, but MYD88 was not mutated (Mareschal et al , ). Whole‐body positron emission tomography/computed tomography excluded any lymph node or visceral involvement.…”
mentioning
confidence: 99%